Investigation on swelling behavior of sodium alginate/black titania nanocomposite hydrogels and effect of synthesis conditions on water uptake - K.V. Satheesh Kumar; M. Bindu; Shwetha Suresh; A. Anil; S. Sujoy; A. Mohanan; P. Periyat (Results in Engineering, 2023)
Polymeric nanocomposite hydrogels were developed from a hydrophilic natural polymer, sodium alginate (SA) with black nano crystalline titania (black TiO2) by using ionic cross linker CaCl2, in view of the possible enhancement in properties of SA towards water treatment application. The optimum conditions for the preparation of films were done by varying the amount of cross-linking agent, cross-linking time and the amount of black nano crystalline TiO2. The nanocomposite hydrogels were then characterized by X-ray diffraction studies (XRD), fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). The surface morphologies of the nanocomposite have been examined by using scanning electron microscopy (SEM). The swelling studies and its kinetics have been investigated under diverse PH conditions. Permeability of the gels were assessed in terms of film characteristics and PH. The results proved that the gels exhibit PH sensitivity. Based on the results, we have proposed a possible mechanism of water transport through the gels. The developed SA/black TiO2 nanocomposite hydrogels have been successfully employed for the efficient degradation organic dyes such as methylene blue and malachite green. The experimental results of dye degradation studies have been compared with theoretical models and it has been observed that the dye degradation follows pseudo second order kinetics for both methylene blue and malachite green. By altering the PH, the nanocomposite hydrogels can be broken and spent TiO2 can be recovered.